Сезонные изменения гематологических показателей у сусликов популяций юга Украины - Передрий, Н.С. (Вестник зоологии, 1973)
Seasonal dynamics of total amount of erythrocytes and leucocytes, haemoglobin concentration were investigated in Citellus pygmaeus P a 11. and C. suslicus G ii 1 d. of agrobiocenosis population in the South of the Ukraine. During hibernation in animals of these species leucopeny is pronounced distinctly. but erythrocyte amount and haemoglobin concentration undergo slight changes in this period. In spring leucocytosis is observed in these animals, erythrocyte amount and haemoglobin concentration at this time are minimal. Hematological indices in noun individuals possess some peculiarities. Indices in animals of different population are also different.